Hepatitis C‐specific effector and regulatory CD4 T‐cell responses are associated with the outcomes of primary infection. Issue 12 (25th August 2016) - Keoshkerian, E.; Hunter, M.; Cameron, B.; Nguyen, N.; Sugden, P.; Bull, R.; Zekry, A.; Maher, L.; Seddiki, N.; Zaunders, J.; Kelleher, A.; Lloyd, A. R.; et al.
Summary: Clearance of primary hepatitis C virus (HCV) infection has been associated with strong and broadly targeted cellular immune responses. This study aimed to characterize HCV‐specific CD4+ effector and regulatory T‐cell numbers and cytokine production during primary infection. Antigen‐specific CD4+ T‐cell responses were investigated in a longitudinal cohort of subjects from pre‐infection to postoutcome, including subjects who cleared [n=12] or became chronically infected [n=17]. A cross‐sectional cohort with previously cleared, or chronic infection [n=15 for each], was also studied. Peripheral blood mononuclear cells were incubated with HCV antigens and surface stained for T‐effector (CD4+CD25 high CD134+CD39‐) and T‐regulatory (CD4+CD25 high CD134+CD39+) markers, and culture supernatants assayed for cytokine production. Contrary to expectations, the breadth and magnitude of the HCV‐specific CD4+ T‐cell responses were higher in subjects who became chronically infected. Subjects who cleared the virus had HCV‐specific CD4+ T‐cell responses dominated by effector T cells and produced higher levels of IFN‐γ, in contrast to HCV‐specific CD4+ T‐cell responses dominated by regulatory T cells and more IL‐10 production in those who became chronically infected. Better understanding of the role of antigen‐specific CD4+ T‐cell responses in primary HCV will further define pathogenesis and help guide development of a preventative vaccine.